Sequence analysis of integrated hepatitis B virus DNA during HBeAg-seroconversion - Budzinska, Magdalena A.; Shackel, Nicholas Adam; Urban, Stephan; Tu, Thomas (Emerging Microbes & Infections, 2018)
Hepatitis B virus (HBV) integration into the host cell genome occurs early on in infection and reportedly induces pro-oncogenic changes in hepatocytes that drive HCC initiation. However, it remains unclear when these changes occur during hepatocarcinogenesis. Extensive expansion of hepatocyte clones with a selective advantage was shown to occur prior to cancer formation during the HBeAg-seroconversion phase of chronic HBV infection. We hypothesized that since integrations occur during the early stages of infection, cell phenotype could be altered and induce a selection advantage (e.g., through insertional mutagenesis or cis-mediated activation of downstream genes). Here, we analyzed the enrichment of genomic and functional patterns in the cellular host sequence adjacent to HBV DNA integration events. We examined 717 unique integration events detected in patients who have and have not undergone HBeAg-seroconversion (n = 41) or in an in vitro model system. We also used an in silico model to control for detection biases. We showed that the sites of HBV DNA integration were distributed throughout the entire host genome without obvious enrichment of specific structural or functional genomic features in the adjacent cellular genome during HBeAg-seroconversion. Currently, this is the most comprehensive characterization of HBV DNA integration events prior to hepatocarcinogenesis. Our results suggest no significant selection for (or against) specific cellular sites of HBV DNA integration occur during the clonal expansion phase of chronic HBV infection. Thus, HBV DNA integration events likely represent passenger events rather than active drivers of liver cancer, which was previously suggested.